2017
DOI: 10.1051/matecconf/201710101001
|View full text |Cite
|
Sign up to set email alerts
|

Metal supported on natural zeolite as catalysts for conversion of ethanol to gasoline

Abstract: Abstract.A various of metal supported into natural zeolite was prepared via wet impregnation method. The transition metals impregnated are nickel, cobalt, copper and zinc. The catalytic properties both of physical and chemical properties were characterized by X-ray Diffraction (XRD), Thermo Gravimetri Analysis (TGA)-Differential Scanning Calorimetry (DSC), Surface Area Analyzer-Porositymeter and also gravimetry method for acidity measurement following by the adsorption of organic bases. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Copper-exchanged zeolites are used as active and selective catalysts for many chemical reactions, such as: NO x abatement, oxidation, isomerization, dehydration and many other processes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Attractive catalytic properties of these materials can be related to both the various oxidation states and the occurrence of copper species in different forms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Copper-exchanged zeolites are used as active and selective catalysts for many chemical reactions, such as: NO x abatement, oxidation, isomerization, dehydration and many other processes [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Attractive catalytic properties of these materials can be related to both the various oxidation states and the occurrence of copper species in different forms [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The S BET value of the support (HZSM5) is lower than other materials. The increase in the specific surface area exhibits that metal oxides did not cover the support's pores [3,27], were evenly distributed on the support [3], and did not cause damage to the support [28][29].…”
Section: Xrd and Xrf Analysismentioning
confidence: 99%
“…However, the metal addition to the support (solid acid) often affects the catalyst's crystallinity, specific surface area, and morphology. Meanwhile, several studies showed an excellent catalyst gives a good performance related to the high crystallinity [3], high surface area [4], porous morphology [5,6], and metal distribution on support [5,7]. Therefore, it is crucial to study the effects of metal addition to support the bifunctional catalyst of direct DME synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the other hand, the structure that composes the framework contains several metal impurities that close the pores, cavities, and channels [10]. Therefore, it will inhibit the diffusion between molecules and reduce its ability as an adsorbent for liquid and gaseous wastes [9,11,12], catalysts [13,14,15], drug delivery [16], separator media [5], and ion exchange resin [15].…”
Section: Introductionmentioning
confidence: 99%